ELEVATION OF Î² HUMAN CHORIONIC GONADOTROPIN HORMONE AND FIBRINOGEN CONCENTRATION AS AN IMMUNOPROTECTIVE MECHANISM DURING PREGNANCY. - EHIAGHE, ALFRED FRIDAY; D.E., Agbonlahor; I.J, Ehiaghe; M.I, Ositadima (JOURNAL OF ADVANCES IN BIOLOGY, 2014)
<!-- [if gte mso 9]> <![endif]--> This study was aimed at determining the level of serum Î² human chorionic gonadotropin hormones and fibrinogen concentration of pregnant women in Benin City. Subjects aged between 18 and 42 years participated in the study. Patient consent form was obtained from 240 pregnant women on antenatal visit and 80 aged matched healthy individual on routine checkup. Serum Î² human chorionic gonadotropin hormones and fibrinogen concentration was estimated using enzyme-linked immunosorbent assays methods. Erythrocyte sedimentation rate was estimated using the westergren method. A significant increase (P< 0.05) in serum Î² human chorionic gonadotropin hormones concentration at stage 1 when compared with stage 3, 4 and 2 and it was also observed that ,there was a significant increase (P< 0.05) in fibrinogen concentration and Erythrocyte sedimentation rate at stage 1 when compared with stage 2,3 and 4 . The elevation of Î² human chorionic gonadotropin hormone, fibrinogen concentration and erythrocyte sedimentation rate are immuno adaptive mechanism of the blastocyst to get implanted onto the walls of the endomentrium where it can obtain nourishment and prevent any possible rejection by the maternal immune system. <!-- [if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]-->